Ensuring Peace Environment in Post Conflict Society Through Institutional Engineering; An Indonesian Case Study - Andi Ahmad Yani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2017)
Most studies examine post conflict society based in security and aid management approach for conflict-management. However, some scholars in conflict studies also suggest an institutional design approach to accommodate conflict parties in aftermath regions, which focuses on seeking an appropriate and acceptable “formula” to resolve conflicts. Based on Indonesia’s case, this study proposes a political compromise approach among different parties, at least for core conflict groups, to formulate an institutional framework in ensuring sustainable peace. This study discusses the feasibility of institutional design in order to mitigate dispute escalation in conflict-prone areas in Indonesia through applying theories of centripetalism (Lijphart,1969) and consocialism (Horowitz, 1985). This paper utilizes the analysis tool of Ilievski and Wolff (2011) to analyze the institutional design of conflict resolution Keywords: Post Conflict Governance, Peace Study, Institutional Theory, Indonesian Study